Long-lasting and sex-dependent effects of late lactational maternal deprivation on socioemotional behaviors in adult mice. (16th March 2023) - Fang, Hanlu; Li, Jiabo; Lu, Liuhua; Yang, Jingyu; Feng, Hao; Yin, Xueyong; Wang, Shuang; He, Xinyue; Song, Li; Shi, Yun; Gao, Yuan; Shi, Haishui; et al.
Highlights: Late lactational 15 min/d MD induces antidepressant effects in male adult mice. Late lactational 15 min/d MD increases the social dominance of male adult mice. Late lactational 3 h/d MD decreases the social dominance of female adult mice. Abstract: The lactation period is an important period for individual development and a sensitive period for the behavioral phenotypes and plasticity of individual offspring. Early life experiences (e.g., maternal deprivation (MD) and neglect) have significant long-lasting and dual effects on individual stress reactivities during adulthood. Theoretically, stress inoculation can improve the adaptive capacity of the body, but overstress can lead to dysfunction when adaptive mechanisms fail. To date, the potential effects of late lactational MD on the socioemotional behaviors of mouse offspring during adulthood are still not fully understood. In the present study, mice were subjected to early deprivation by individually separating pups from their dam for 0 min, 15 min, and 3 h per day from PND 13–25. The social dominance test (SDT), social interaction test (SI), open field test (OFT), and forced swim test (FST) were carried out during adulthood. The results showed that the social dominance of male mice in the 15 min/d MD group significantly increased, especially in low-rank mice. In the 3 h/d MD group, the social dominance of female mice was decreased, especially in the lower-rank mice. The anxiolytic and antidepressant-like effects of the 15 min/d MD group were significantly increased in male mice. Our study provides direct evidence that MD during late lactation period results in long-lasting effects on social dominance as well as on anxiety and depression phenotypes in a sex-dependent manner.